2018
DOI: 10.1155/2018/5053709
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Disorders among Dutch Adolescents: Prevalence and Biological, Psychological, and Social Risk Indicators

Abstract: Aims To assess the prevalence rates of pain-related temporomandibular disorders (TMDs) and temporomandibular joint (TMJ) sounds in a large group of Dutch adolescents, aged between 12 and 18 years and to determine if the same biological, psychological, and social risk indicators are related to both TMD pain and TMJ sounds. Methods In this cross-sectional questionnaire survey, 4,235 questionnaires were analyzed, with an about equal gender distribution. Results The overall prevalence of pain-related TMDs was 21.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
26
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 40 publications
7
26
0
4
Order By: Relevance
“…The prevalence of self-reported intraarticular symptoms corroborates the results of a previous German cohort and of previous investigations of adolescents from different nationalities, all of which revealed that 14.0%-19.3% of the study subjects reported TMJ sounds, 3,5,6,14 and approximately 5% describe jaw locking. 5 Regarding TMD pain, the values given in the results were considerably lower than in most observations 2,13 but comparable to results from Swedish adolescents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of self-reported intraarticular symptoms corroborates the results of a previous German cohort and of previous investigations of adolescents from different nationalities, all of which revealed that 14.0%-19.3% of the study subjects reported TMJ sounds, 3,5,6,14 and approximately 5% describe jaw locking. 5 Regarding TMD pain, the values given in the results were considerably lower than in most observations 2,13 but comparable to results from Swedish adolescents.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the prevalence of TMD, the most ambivalently discussed risk factors are cultural background, gender, psychosocial factors, general health and pubertal development or age, respectively. [5][6][7][8] The study results are heterogeneous but define a tendency of female adolescents presenting higher prevalence values. 5 The development of dentition might be an influencing factor for TMJ sounds that can increase from primary to permanent dentition.…”
Section: Backg Rou N Dmentioning
confidence: 88%
“…Abnormal disc position or disc displacement has often been diagnosed in patients of diverse populations and can occur even in the growing population and is considered to be a condition that may worsen over time 10,11 . It has been observed that disc displacement of the TMJ is able to produce pain, 10 dysfunction and bone changes in the joint surfaces 10,12,13 …”
Section: Introductionmentioning
confidence: 99%
“…Se sabe que los factores psicológicos desempeñan un importante papel en la etiología y persistencia del trastorno temporoandibular (TTM) 9 . Según Marpaung et al 10 , una forma de clasificar los diferentes tipos de TTM es dividiéndolos en dos amplias categorías: TTM relacionados con el dolor y TTM intraarticulares. En la primera categoría el dolor puede originarse a partir de las ATM, pero con mayor frecuencia los músculos masticatorios están involucrados.…”
Section: Discussionunclassified